A review on medicinal plants with hypolipidemic activity - G.Alagumanivasagam; P.Veeramani (International Journal of Pharmacy and Analytical Research, 2015)
In the last few years there has been an exponential growth in the field of herbal medicine and these drugs are gaining popularity both in developing and developed countries because of their natural origin and less side effects. There are a growing number of studies reporting hypolipidemics activity with traditional medicines. The present review constituents on plant with hypolipidemic activity from this plants and special emphasis on those found in different regions all over the world, including mainly India. The information is recorded in plant scientific name, family, part used, route of administration, dose given, Method used (Pharmacological method) and references. The advantages of herbal medicines reported are effectiveness, safety, affordability, and acceptability. The present review focus on the botanical sources, Phytochemistry, Therapeutic uses, potential Pharmacological effect of some of the herbs, and Siddha formulations, being used in Siddha system of medicine for urolithiasis.